2018
DOI: 10.1111/jcmm.13931
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 increases migration and proliferation of human glioblastoma cells by activating transient receptor potential melastatin 7 channels

Abstract: Recent studies showed that both prostaglandin E2 (PGE2) and transient receptor potential melastatin 7 (TRPM7) play important roles in migration and proliferation of human glioblastoma cells. In this study, we tested the association between PGE2 and TRPM7. We found that PGE2 increased TRPM7 currents in HEK293 and human glioblastoma A172 cells. The PGE2 EP3 receptor antagonist L‐798106 abrogated the PGE2 stimulatory effect, while EP3 agonist 17‐phenyl trinor prostaglandin E2 (17‐pt‐PGE2) mimicked the effect of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Prostaglandin E2 (PGE2) plays a role in the migration and proliferation of human glioblastoma cells [ 111 ]. Tian et al [ 111 ] observed that PGE2 increased TRPM7 currents in human glioblastoma A172 cells.…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
See 2 more Smart Citations
“…Prostaglandin E2 (PGE2) plays a role in the migration and proliferation of human glioblastoma cells [ 111 ]. Tian et al [ 111 ] observed that PGE2 increased TRPM7 currents in human glioblastoma A172 cells.…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Prostaglandin E2 (PGE2) plays a role in the migration and proliferation of human glioblastoma cells [ 111 ]. Tian et al [ 111 ] observed that PGE2 increased TRPM7 currents in human glioblastoma A172 cells. Knockdown of TRPM7 by shRNA or exposure of cells to NS8593 abrogated PGE2-stimulated motility and proliferation of A172 cells [ 111 ].…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
See 1 more Smart Citation
“…FYGL has dose-dependent hypoglycemic and hypolipidemic effects and could increase blood insulin levels. Furthermore, it inhibited the overexpression of PTP1B, enhanced insulin-stimulated glycogen synthesis, and decreased blood glucose in a mouse model of insulin resistance (Tian et al 2018). FYGL can ameliorate type 2 diabetes mellitus caused by mitochondrial dysfunction and can decrease ROS level (Yang et al 2019).…”
Section: Hypoglycemic Effectmentioning
confidence: 99%
“…Modern pharmacology has shown that G. lucidum has antitumor (Kao et al 2016), anti-inflammatory (Liu et al 2018), and antioxidation effects (Sarnthima et al 2017) and that it could regulate the respiratory, nervous, and immune systems (Kubota et al 2018). G. lucidum also has a hypoglycemic effect (Tian et al 2018) and can protect the liver (Wu et al 2016). Nowadays, G. lucidum is used as a powder, tea, and dietary supplement.…”
Section: Introductionmentioning
confidence: 99%